2004
DOI: 10.1051/0004-6361:20034630
|View full text |Cite
|
Sign up to set email alerts
|

Time damping of linear non-adiabatic magnetohydrodynamic waves in an unbounded plasma with solar coronal properties

Abstract: Abstract.In this paper, we study the time damping of magnetoacoustic waves when the adiabaticity assumption is removed by means of an energy equation which includes optically thin radiative losses, thermal conduction and heating. For the sake of simplicity, this study has been done for a homogeneous, isothermal and unbounded medium permeated by a uniform magnetic field, with physical properties akin to those of the corona, the prominence-corona transition region (PCTR) and prominences. In some PCTR regimes and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
73
0
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 66 publications
(81 citation statements)
references
References 27 publications
6
73
0
2
Order By: Relevance
“…Turning our attention to the slow wave (Fig. 2c), we see that the maximum and the right hand side minimum of τ D /P are also slightly shifted toward lower values of k. Results from Carbonell et al (2004) and Forteza et al (2008) indicate that thermal conduction is responsible for the maximum and minimum of τ D /P. Thus, the additional contribution of neutral helium atoms to thermal conduction (Eq.…”
Section: Free Propagation In An Unbounded Mediummentioning
confidence: 85%
See 1 more Smart Citation
“…Turning our attention to the slow wave (Fig. 2c), we see that the maximum and the right hand side minimum of τ D /P are also slightly shifted toward lower values of k. Results from Carbonell et al (2004) and Forteza et al (2008) indicate that thermal conduction is responsible for the maximum and minimum of τ D /P. Thus, the additional contribution of neutral helium atoms to thermal conduction (Eq.…”
Section: Free Propagation In An Unbounded Mediummentioning
confidence: 85%
“…In a subsequent work (Forteza et al 2008), they extended their previous analysis by considering radiative losses and thermal conduction by electrons and neutrals. Their main results with respect to the fully ionized case (Carbonell et al 2004) were, first of all, that ion-neutral collisions (by means of the so-called Cowling's diffusion) can damp both Alfvén and fast waves but non-adiabatic effects remain only important for the damping of slow and thermal waves, and second, that critical values of the wavenumber exist in which the real part of the frequency vanishes, so wave propagation is impossible for larger wavenumbers. Again, applications to a more complex cylindrical geometry have also been performed (Soler et al 2009b,c).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, for fully ionised plasmas, the time damping of prominence oscillations has been studied by considering non-adiabatic MHD waves, including the effects of optically thin radiation, thermal conduction, and heating, in unbounded and bounded prominence slabs (Carbonell et al 2004;Terradas et al 2005), prominence slabs surrounded by an infinite solar corona (Soler et al 2007) and bounded prominence-corona slabs (Soler et al 2009c). On the other hand, taking into account the fine prominence structure, and assuming that the threads forming solar filaments can be modeled as cylindrical flux tubes filled with fully ionised prominence plasma surrounded by the solar corona, the time damping of inhomogeneous cylindrical flux tubes due to resonant absorption has been studied by Arregui et al (2008).…”
Section: Introductionmentioning
confidence: 99%
“…This means that for a typical period of 10 3 s, the damping length would be between 10 2 and 10 3 km, the wavelength around 10 3 km and, as a consequence, in a distance smaller than a wavelength the slow wave would be strongly attenuated. On the other hand, during our calculations, we have found that the different heating mechanisms usually considered (Carbonell et al 2004) do not affect the results.…”
Section: Discussionmentioning
confidence: 53%
“…These small-amplitude oscillations have been commonly interpreted in terms of linear magnetohydrodynamic (MHD) waves and the damping of oscillations has been studied by considering different dissipative mechanisms. For instance, in the case of fully ionised plasmas, the time damping of prominence oscillations has been studied by considering non-adiabatic MHD waves, including the effects of optically thin radiation, thermal conduction, and heating, in unbounded and bounded prominence plasmas (Carbonell et al 2004;Terradas et al 2005). By assuming that the threads of which the solar filaments consist can be modeled as cylindrical flux tubes, the time damping of homogeneous and inhomogeneous cylindrical flux tubes, with prominence physical conditions, has been modeled using thermal mechanisms and resonant absorption, respectively (Soler et al 2008;Arregui et al 2008;Soler et al 2009b).…”
Section: Introductionmentioning
confidence: 99%